LEGAL ISSUES ON THE ATTACKS AGAINTS VESSELS IN THE STRAITS OF MALACCA - Putri, Siti Noor Malia (UI Scholars Hub, 2014)
Piracy that occurs in the straits of Malacca has become a serious problem that need to be solved. The United Nations Office on Drugs and Crime (UNODC) has been combating piracy in this particular area since 2009. In an attempt to do so, UNODC creates a Counter Piracy Program (CPP) that has been implemented in several African Countries. However, UNODC doesn’t define the limitation of piracy which described in 1982 UNCLOS that only defines it as piracy on high seas. Whereas, piracy is not only takes place on high seas but also within territories of the states jurisdiction. The lack of ability to implement the provisions in national scope become another problem in regards preventing piracy in the Straits of Malacca.